Faktor-Faktor Penyebab Skizofrenia(Studi Kasus Di Rumah Sakit Jiwa Daerah Surakarta) - Fatmawati, Iin Nadlifa Arwah, Dr. Moordiningsih, M.Si, Psi (2016)
The aim of this research are to determine the causal factors of schizophrenia and the Javaness family's effort to heal the schizophrenia. This study used a qualitative approach, data collection using interviews and observation techniques. Informants in this study were selected by purposive sampling, the informant were 8 people who are the closest relatives of patients and know the patient's daily activities. Meanwhile, the supporting informants are people who have information which is not shared by key informants. This study found that the causal factors of schizophrenia occurrence are genetic, environmental, and psychological factor. An interesting finding of this study is thatsupernatural factors like possession become one of thecause of schizophrenia and did the supernatural to effort the healing like going to traditional healers or did 'rukyah' before the family finally find out information about a mental hospital from neighbors or others.